(untitled) (JURNAL PROTEKSI KESEHATAN, 2024)
Carrot seed oil, rich in vitamin A, is known as an antioxidant, sun protectant, and anti-aging and skin rejuvenating agent. This research aims to evaluate the formulation and antioxidant potential of carrot seed oil spray. The research method consists of three stages: formulation, physical evaluation, and antioxidant activity test. The organoleptic test results showed color differences in the three formulas. All three formulas have a thick, oily consistency and the distinctive aroma of carrot seed oil. The average pH value of F1 is 7.4, F2 is 7.7, and F3 is 8.0. The viscosity value of F1 is 25.4 cP, F2 is 19.56 cP, and F3 is 31.66 cP. The antioxidant activity test shows that pure carrot seed oil has moderate antioxidant activity with an IC50 value of 240.9772 g/mL. The three carrot seed oil spray formulas showed weak antioxidant activity with IC50 values: F1 269.3943 g/mL, F2 316.1039 g/mL, and F3 442.6015 g/mL. Based on research, it can be concluded that pure carrot seed oil has moderate antioxidant activity, while the three carrot seed oil spray formulas have weak antioxidant activity.